Burkholderia cenocepacia ETR-B22 volatile organic compounds suppress postharvest grey mould infection and maintain aroma quality of tomato fruit. (1st August 2022) - Chen, Jianhua; Wei, Xiaolan; Lu, Xuan; Ming, Ruhong; Huang, Ding; Yao, Yuqun; Li, Liangbo; Huang, Rongshao
Abstract: Microbial volatile organic compounds (VOCs) are effective biofumigants for controlling postharvest fruit decay. We evaluated the postharvest biofumigation efficacy of the VOCs produced by Burkholderia cenocepacia ETR-B22 for alleviating tomato fruit grey mould and its impact on the fruit quality. The results demonstrated that the VOCs inhibited the hyphal growth and spore germination of pathogen Botrytis cinerea and caused hyphal cell death. Postharvest biofumigation with VOCs significantly decreased disease incidence, disease index, and weight loss of tomato fruit. The antifungal efficacy of the VOCs was affected by growth media substrates, inoculation volume, and concentration. Among the analysed VOC components, dimethyl trisulfide was most effective in inhibiting B. cinerea . Biofumigation with VOCs produced by ETR-B22 delayed the deterioration of the nutrition quality of tomato fruit. Metabolomics analysis revealed that the aromatic metabolite profile of postharvest tomato fruit was well-maintained after fumigation with ETR-B22 VOCs. Therefore, B. cenocepacia ETR-B22 VOCs could be used as useful biofumigants for extending postharvest tomato fruit shelf life and controlling grey mould disease. Graphical abstract: Image 1 Highlights: Post-harvest biofumigation of tomato fruit inhibited grey mould disease development. Burkholderia cenocepacia ETR-B22 volatiles supressed Botrytis cinerea infection. Bacterial volatiles supported stored tomato fruit nutritional quality maintenance. Biofumigation delayed aroma quality decline in tomato fruit. Efficacy of bacterial volatiles varied with incubation methods and conditions.